PENGGUNAAN MODEL THINK TALK WRITE DENGAN MEDIA GAMBAR DALAM PENINGKATAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI PADA SISWA KELAS IV SDN 6 PANJER TAHUN AJARAN 2015/2016 - Megasari, Nila (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Think Talk Write Using Picture Media in Improving Writing Skills of Descriptive Text for the Fourth Grade Students of SDN 6 Panjer in the Academic Year of 2015/2016. The objectives of this collaborative Classroom Action Research (CAR) is to improve writing skills of descriptive text in using Think Talk Write using picture media. This research was conducted within three cycles in six meetings. Each cycle consisted of planning, action, observation, and reflection.Subjects of the research were 28 students. The results of this research showed thatthe use of Think Talk Write using picture media can improve writing skills of descriptive text. The conclusion of this research is the use of Think Talk Write using picture media can improve writing skills of descriptive text for the fourth grade students of SD Negeri 6 Panjer in the academic year of 2015/2016. Keywords: Think Talk Write, picture media, writing skills Abstrak: Penggunaan Model Think Talk Write dengan Media Gambar dalam Peningkatan Keterampilan Menulis Karangan Deskripsi pada Siswa Kelas IV SDN 6 Panjer Tahun Ajaran 2015/2016. Tujuan Penelitian Tindakan Kelas Kolaboratif ini adalah untuk meningkatkan keterampilan menulis karangan deskripsi melalui penggunaan model Think Talk Write dengan media gambar. Penelitian ini dilaksanakan dalam tiga siklus dengan tahapan perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian berjumlah 28 siswa. Hasil penelitian menunjukkan penggunaan model Think Talk Write dengan media gambar dapat meningkatkan keterampilan menulis karangan deksripsi. Simpulan penelitian ini adalah penggunaan model Think Talk Write dengan media gambar dapat meningkatkan keterampilan menulis karangan deksripsi pada siswa kelas IV SDN 6 Panjer tahun ajaran 2015/2016. Kata Kunci: model Think Talk Write, media gambar, keterampilan menulis